Increase Energy Efficiency By Improving The Heating System In Buildings (American Innovator: Journal of Emerging Technologies and Research, 2026)
In this scientific article the issue of energy efficiency improvement by improving the heating system in administrative buildings on the basis of an energy audit is analyzed. The article examines the importance of heat energy spent to ensure a favorable microclimate in the building, losses in pipeline networks, the state of operation of radiators, hydraulic balance, the useful work coefficient of the boiler device and automatic control means. The calculations compared the area and volume of the building to be heated, indoor and outdoor air temperatures, heat loss due to ventilation, and the conditions of the heating system before and after modernization. The results showed that by making a comprehensive improvement of the heating system, heat consumption can be significantly reduced.
Keywords: energy audit; heating system; heat loss; boiler FIC